Trump's Potential Reelection and the Fate of Immigrants - Mariita, Pacificah (International Journal of Language and Literary Studies, 2024)
This paper examines the impact of Trump's presidential reelection on immigrants in the upcoming elections. A thorough exploration of Trump's travel bans, border wall construction, family separation, termination of DACA, and slogans such as MAGA provides context on what people should expect in his second term and the perceptions held by the majority of his supporters, who are predominantly working-class White voters disappointed by outcomes of previous governments. This study outlines these issues based on an assessment of various publications addressing the topic within the past five years and considering the impact of Trump’s nationalist and populist policies towards undocumented persons and comparing them to those of Biden and Obama, legal lawsuits against Trump, and the role of advocates in resolving the problems with immigration. These articles reveal that Trump has taken a discriminatory approach to the issue of immigration. At the same time, his counterparts are more lenient on foreigners because they understand the benefits the United States would receive from this engagement, such as access to labor while stabilizing the economy through additional revenue. Trump's attitude presents ideologies that would jeopardize the country's social and economic state if he is reelected in the upcoming elections.